Leaf ionome signatures as drought tolerance indicators in chilli - Venkata Ramana, Muddarsu; Manivannan, Subramanian; Upadhyay, Sujata; Umadevi, Palaniyandi (Frontiers in Plant Science, 2025)
Chilli (Capsicum annuum L.) cultivation is confined to warm and semi-arid regions where irrigation availability is often limiting production. Drought is one of the constraints of chilli cultivation. Hence, the development of drought-tolerant varieties is increasingly essential, and efforts are directed towards developing methods to understand chilli plant responses to water deficit. In this context, we used ionomics to study the drought tolerance of chilli. The ionome profiling of leaves using inductively coupled plasma mass spectrometry (ICP-MS) and integrating it with morpho-physiological and biochemical characteristics of eight cultivars using principal component and correlation analyses revealed the signature ionome mediating varying levels of drought tolerance. The accumulation of Ca, Cu, Mg, Fe, Mn, Mo, Ni, and Sn ions in leaves indicated them as markers for drought tolerance in chilli. This is a major step towards the identification of drought-tolerant cultivars using a simple and efficient technique in chilli. This method can serve as a simple, modern high-throughput tool in pre-breeding for selecting the drought-tolerant genotypes in crop improvement programmes.